SABERES E PRÁTICAS DOCENTES EM CURSOS DE LATO SENSU - Gonçalves, Adriana Camolesi (2013)
According to data from INEP National Institute for Educational Research (2007), there are around 8,866 lato sensu courses in Brazil, and consequently the number of professors who teach at higher education has increased, once we consider 2010 s Census of Higher Education, in which 345,335 bonds of higher education teaching were registered. Based on these facts, the following questions raised: what are the professors pedagogic knowledge and practice in relation to their teaching at lato sensu? How have the professors who teach at this segment become teachers once their education is not always pedagogic? The level of education needed to teach at this segment is set forth in article 66 of the Law of Guidelines and Bases for Education, which states that the preparation to teach at higher education is done through Post-Graduation, being Master s and/or Doctor s Degree programs priority and it is known that the indication of pedagogic education is not mandatory for one to become a professor. Therefore the research about the aforementioned questions was done through a survey about these professors educational and professional paths, so we could identify whether the lack on pedagogic education influences or has influenced their teaching knowledge and practice. Also, we wanted to know how they have built their professor identities throughout their careers, and what their real motivation to becoming teachers is. Four professors who teach at a private institution of higher education in São Paulo/ SP were interviewed. Semi-structured interviews were done as a tool for data collection, and the organization of the category analysis was done through the content analysis method. The survey also had a historic contextualization about the laws of lato sensu, and a theoretic discussion about teaching knowledge and practice focused on higher education.The data analysis has confirmed the hypothesis that those who teach at lato sensu have gotten their knowledge and practice from what they experienced when they were students, using the references they had throughout their educational and professional paths as role models. It was verified that, most of the times, the professors only seek pedagogic education after being involved in the teaching at lato sensu, depending almost exclusively on their own decisions, once the laws do not predetermine the profile of the professors who teach at this segment. Hence, they gradually become professors, and the pedagogic education is rather a possibility of practice, once the professional experiences they have in their area come first.